Immediate Re-Insertion of Non-Autologous Materials in Revision Augmentation Rhinoplasty. Issue 5 (May 2015) - Kim, Yoo Suk; Hyun, Dong Woo; Seong, Sang Yeob; Park, Do Yang; Kim, Chang-Hoon; Yoon, Joo-Heon
<x xml:space="preserve">Abstract</x> Objective This paper aims to study whether immediate re-insertion of non-autologous augmentation material in revision augmentation rhinoplasty is a safe surgical strategy creating a successful and functional aesthetic outcome. Study Design Retrospective review and analysis of medical records. Setting Tertiary referral hospital. Subjects and Methods A retrospective analysis of 11 consecutive patients who had undergone removal of previous augmentation material and immediate re-insertion of non-autologous material in revision augmentation rhinoplasty was performed. Demographics, surgical approaches, augmentation materials, material-related complications, time interval between surgeries, surgical outcome, and follow-up period were included in the analysis to evaluate our surgical strategy. Results A successful surgical outcome with respect to both functional and aesthetic aspects was obtained in nine of the 11 enrolled patients. In 1 patient, there was a recurrence of material-related complication, while another patient experienced unsatisfactory graft displacement. The unsuccessful cases had 2 common features in that silicone and endonasal approaches were used in the primary and revision surgeries, respectively. Conclusion Removal of previous augmentation material and immediate re-insertion of non-autologous material for dorsal augmentation in revision rhinoplasty is feasible with respect to functional and aesthetic aspects of patient outcome.